Áillohaš and His Image Drum: The Native Poet as Shaman - Dana, Kathleen Osgood (Nordlit, 2011)
In this article, I will look particularly at the work of Áillohaš (the Sámi name for poet Nils-Aslak Valkeapää) and his pivotal work Beaivi, Áhčážan (The Sun, My Father). A deep reading of a number of poems from Beaivi, Áhčážan will provide the substance of this discussion.